2007
DOI: 10.1359/jbmr.07s201
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Calcium Homeostasis, and Skeleton Accretion in Children

Abstract: Overt vitamin D deficiency early in life has classically been associated with the etiology of rickets. Recent interest has focused on vitamin D insufficiency and calcium homeostasis and bone health. A review of the literature suggests that the relationship between vitamin D status and calcium utilization has some important differences with life stage and race. In contrast to adults, serum 1,25-dihydroxyvitamin D, but not serum 25-hydroxyvitamin D, predicts calcium absorption in growing children. PTH suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Studies on the effects of vitamin D supplementation or status on bone health have yielded mixed results in children [22] and Dairy and Bone Health 84S VOL. 28, NO.…”
Section: Vitamin D and Bone Healthmentioning
confidence: 99%
“…Studies on the effects of vitamin D supplementation or status on bone health have yielded mixed results in children [22] and Dairy and Bone Health 84S VOL. 28, NO.…”
Section: Vitamin D and Bone Healthmentioning
confidence: 99%
“…Such associations suggest a possible role for maternal and foetal nutrition in determining peak bone mass and fracture risk in later life. The observation of altered skeletal structure as a consequence of undernutrition during a critical stage of early life, as exemplified by rickets, demonstrates that skeletal development can be disrupted by severe dietary change [10]. Cohort studies of female twins, including monozygous twins, showed significant intra-pair concordance between birth weight and bone mass.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblast growth factor 23, elevated in patients with some tumors and hypophosphatemic forms of rickets, can also suppress 1-hydroxylation [34]. 1,25-Dihydroxyvitamin D binds to vitamin D receptors in the intestine to stimulate transcellular absorption of calcium and phosphorus [35]. In addition, there is separate paracellular calcium absorption which depends on the dietary calcium content but not on 1,25-dihydroxyvitamin D [35].…”
Section: Physiology and Pathophysiology Of Vitamin D Metabolismmentioning
confidence: 99%
“…1,25-Dihydroxyvitamin D binds to vitamin D receptors in the intestine to stimulate transcellular absorption of calcium and phosphorus [35]. In addition, there is separate paracellular calcium absorption which depends on the dietary calcium content but not on 1,25-dihydroxyvitamin D [35]. Inadequate calcium intake could cause insufficient intestinal calcium absorption through both the trans-cellular and the para-cellular routes to meet the needs of the body.…”
Section: Physiology and Pathophysiology Of Vitamin D Metabolismmentioning
confidence: 99%